2021
DOI: 10.1111/bjh.17281
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of relapsed and refractory nodular lymphocyte‐predominant Hodgkin lymphoma: a North American analysis

Abstract: Nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) is a rare entity, with limited data on the outcome in the relapsed/refractory setting. We evaluated the outcome of all patients diagnosed between 04/1979 and 01/2019 with relapsed or progressive NLPHL after initial active therapy at two institutions, refractory disease being defined as lack of response to treatment and/or relapse within three months of treatment. NLPHL patients with histological evidence of transformation at time of first relapse or progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Whilst the clinical outcome for most patients with NLPHL is very good, a small number will relapse; some with multiple, often late, relapses. Most patients with recurrent or poorly responsive disease respond to additional immunochemotherapy and/or radiotherapy 15,35,63,64 . Clinical relapse must be confirmed histologically to exclude diffuse large B‐cell lymphoma (DLBCL) transformation before initiating second‐line treatment.…”
Section: Imaging During Treatment and At The End Of Treatment (Adults...mentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the clinical outcome for most patients with NLPHL is very good, a small number will relapse; some with multiple, often late, relapses. Most patients with recurrent or poorly responsive disease respond to additional immunochemotherapy and/or radiotherapy 15,35,63,64 . Clinical relapse must be confirmed histologically to exclude diffuse large B‐cell lymphoma (DLBCL) transformation before initiating second‐line treatment.…”
Section: Imaging During Treatment and At The End Of Treatment (Adults...mentioning
confidence: 99%
“…Most patients with recurrent or poorly responsive disease respond to additional immunochemotherapy and/or radiotherapy. 15,35,63,64 Clinical relapse must be confirmed histologically to exclude diffuse large B-cell lymphoma (DLBCL) transformation before initiating second-line treatment. Treatment approaches at relapse have included single-agent monoclonal anti-CD20 rituximab or ofatumumab, 65 conventional chemotherapy such as ABVD, BEACOPP, DHAP (dexamethasone, cytarabine and cisplatin) with or without radiotherapy and high-dose chemotherapy followed by autologous stem cell rescue.…”
Section: Treatment Of Relapsed And/or Refractory Nlphlmentioning
confidence: 99%
“…This finding underscores that NLPHL mostly has an indolent course and a very good prognosis even in case of multiple relapses. 3,4,9,10 Taken together, the present study demonstrated that a significant proportion of individuals with relapsed NLPHL did not achieve long-term remission after treatment with fixed-duration single-agent ibrutinib. Thus, most patients with NLPHL recurrence are no candidates for treatment with this approach.…”
Section: F I G U R Ementioning
confidence: 51%
“…7,8 The male predominance among patients treated within the present study is consistent with earlier analyses. 3,4,7,8 Study treatment with ibrutinib was generally well tolerated.…”
mentioning
confidence: 99%
“…This limit is described in other papers focused on this theme due to a lack of consensus on the role of autologous SCT or other regimens. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%